EFFECT OF HOSPITAL ACREDITATION ON UNDERFIVE INFANT MORTALITY RATE IN INDONESIA - Dinda Ayu Pramesty; Titik Umaiyah Haryanti; Galuh Lailatul Fitriyani; Fahmi Arif Kurnianto; Fahrudi Ahwan Ikhsan (MAJALAH PEMBELAJARAN GEOGRAFI, 2019)
As a developing country Indonesia is one country that has a high mortality rate, especially infant mortality rate (IMR). Infant mortality is an important indicator to show the state of health status in a country. Infant mortality rate is a number indicating the number of deaths of 0 years of age from every 1000 live births in a given year or can be said to be the probability of a baby dies before reaching the age of one year. Data collection techniques in this study using secondary data sourced from BPS and kemenkes. Data analysis used is product moment correlation to know strength of relationship between two variables. From the calculation using the formula obtained results -0.450044898. According to the data that has been obtained by using the research methods listed above, it can be concluded that the relationship of IMR data 2017 and hospital accreditation has a strong correlation relationship.This can be seen from several indicators that affect hospital accreditation, among others, service convenience and quality of health services, facilities and infrastructure, and the availability of qualified doctors and nurses that can affect infant mortality in Indonesia. Keyword: developing country, facilities and infrastructure, mortality rate Azwar, Azrul. 1996. Pengantar Administrasi Kesehatan. Binarupa Aksara; Jakarta. Lissauer T, Fanaroff A.2009.At a Glance Neonatologi.Erlangga: Jakarta Mantra, I.B. 2000. Demografi Umum. Yogyakarta : Pustaka Pelajar. Mochtar, Rustam. 1998. Sinopsis Obstetri: obstetri fisiologi, obstetri patologi. Edisi Dua. Jakarta; EGC: Hal 218-220 Simbolon, D., Chalidyanto, D., dan Ernawati (2013) Determinan Kinerja Pelayanan Kesehatan Ibu dan Anak di Rumah Sakit Pemerintah Indonesia (Analisis Data Rifakes 2011). JKKI Vol 02 No 04:202-14 Sutoto et al., 2012. Instrumen Akreditasi Rumah Sakit Standar Akreditasi Versi 2012 1st ed., Jakarta. Utomo, B. 1985. Dasar-Dasar Demografi. Jakarta : Lembaga Demografi Fakultas Ekonomi Universitas Indonesia. Vivian Dewi.2010.Asuhan Neonatus Bayi dan Anak Balita.Salemba Medika: Jakarta Ari Sulistyawati, (2009), Tumbang,status gizi,dan imunisasi dasar , Numed, Yogyakarta. Bachroen, Cholis dan Soeharsono soemantri. 1988. Penelitian Indikator “Proxy” Dari Angka Kematian Bayi. Surabaya: Departemen Kesehatan RI-Badan Penelitian Dan Pengembangan Kesehatan. Bakti Husada. IFA, Hoday et al. ANALISIS SOSIAL EKONOMI TERHADAP TINGKAT KESEJAHTERAAN MASYARAKAT TENGGER GUNUNG BROMO.MAJALAH PEMBELAJARAN GEOGRAFI, [S.l.], v. 2, n. 1, p. 169-175, june 2019. ISSN 2622-125X. Available at: <https://jurnal.unej.ac.id/index.php/PGEO/article/view/12305>. Date accessed: 12 aug. 2019. PAHLEVY, Fahrizal Novan; APRIYANTO, Bejo; ASTUTIK, Sri. KARAKTERISTIK SOSIAL EKONOMI MASYARAKAT DAERAH WISATA BROMO SEBAGAI PENGEMBANGAN KESEJAHTERAAN HIDUP. MAJALAH PEMBELAJARAN GEOGRAFI, [S.l.], v. 2, n. 1, p. 172-189, june 2019. ISSN 2622-125X. Available at: <https://jurnal.unej.ac.id/index.php/PGEO/article/view/12177>. Date accessed: 12 aug. 2019. HARYANTI, Titik Umaiyah. PERANAN PANTAI DALAM KONDISI SOSIAL EKONOMI MASYARAKAT DISEKITAR PANTAI BENTAR KABUPATEN PROBOLINGGO JAWA TIMUR.MAJALAH PEMBELAJARAN GEOGRAFI, [S.l.], v. 1, n. 1, p. 12-16, aug. 2018. ISSN 2622-125X. Available at: <https://jurnal.unej.ac.id/index.php/PGEO/article/view/8336>. Date accessed: 12 aug. 2019. UMAM, Muhammad Fikri; ALHIDAYAH, Yazid; FAUZIYAH, Rita. ANALISIS MATERIAL ENDAPAN VULKAN GUNUNG SEMERU KABUPATEN LUMAJANG. MAJALAH PEMBELAJARAN GEOGRAFI, [S.l.], v. 2, n. 1, p. 92-98, june 2019. ISSN 2622-125X. Available at: <https://jurnal.unej.ac.id/index.php/PGEO/article/view/11522>. Date accessed: 12 aug. 2019. SETYAWAN, Muhammad Alif; APRIYANTO, Bejo; ASTUTIK, Sri. ANALISIS KARAKTERISTIK ENDAPAN MARINE DAN PENGARUHNYA BAGI SEKTOR PERTANIAN DAN PERAIRAN DI PESISIR SELATAN PANTAI PANCER KECAMATAN PUGER KABUPATEN JEMBER JAWA TIMUR. MAJALAH PEMBELAJARAN GEOGRAFI, [S.l.], v. 2, n. 1, p. 141-154, june 2019. ISSN 2622-125X. Available at: <https://jurnal.unej.ac.id/index.php/PGEO/article/view/11760>. Date accessed: 12 aug. 2019. KURNIANTO, Fahmi Arif et al. THE ENVIRONMENT ANALYSIS OF POPULATION GROWTH, UNEMPLOYMENT, AND POVERTY LEVEL IN MAESAN DISTRICT BONDOWOSO REGENCY. Geosfera Indonesia, [S.l.], v. 3, n. 2, p. 113-121, aug. 2018. ISSN 2614-8528. Available at: <https://jurnal.unej.ac.id/index.php/GEOSI/article/view/8439>. Date accessed: 12 aug. 2019. doi: https://doi.org/10.19184/geosi.v3i2.8439. SARI, Eva Kurnia; PRAMESTY, Dinda Ayu. THE EFFECT OF VEHICLES INTENSITY IN SUMBERSARI JEMBER REGENCY. Geosfera Indonesia, [S.l.], v. 3, n. 3, p. 50-58, jan. 2019. ISSN 2614-8528. Available at: <https://jurnal.unej.ac.id/index.php/GEOSI/article/view/9300>. Date accessed: 12 aug. 2019. doi: https://doi.org/10.19184/geosi.v3i3.9300. LESTARI, Dwi et al. ANALISIS FENOMENA GEOGRAFI FISIK PADA PENGUKURAN PROSES DAN HASIL PROSES BENTANG ALAM JAWA TENGAH. MAJALAH PEMBELAJARAN GEOGRAFI, [S.l.], v. 2, n. 1, p. 110-118, june 2019. ISSN 2622-125X. Available at: <https://jurnal.unej.ac.id/index.php/PGEO/article/view/11626>. Date accessed: 12 aug. 2019. ZAHROH, Faidatuz; ELFIANI, Vira; H, Arya Bagas. ASPEK SOSIAL DAERAH KARST PUGER DALAM PRESPEKTIF EKONOMI. MAJALAH PEMBELAJARAN GEOGRAFI, [S.l.], v. 2, n. 1, p. 155-160, june 2019. ISSN 2622-125X. Available at: <https://jurnal.unej.ac.id/index.php/PGEO/article/view/11780>. Date accessed: 12 aug. 2019. NURIYANTO, Muhammad Zaid; FIRMANSYAH, Fahrul Agil; PRASETYONO, Ica. ANALISIS PERUBAHAN BENTANG GEOMORFOLOGI PANTAI BENTAR KABUPATEN PROBOLINGGO.MAJALAH PEMBELAJARAN GEOGRAFI, [S.l.], v. 2, n. 1, p. 99-109, june 2019. ISSN 2622-125X. Available at: <https://jurnal.unej.ac.id/index.php/PGEO/article/view/11523>. Date accessed: 12 aug. 2019.